Desenvolvimento de barras de cereais com alto teor de fibras e vitaminas por meio de delineamento experimental - Covino, Roberta (2012)
Current changes in food consumption due to the demands generated by new urban way of life makes people need to restructure their lives according to the time, financial resources available to local food, shopping, among others. Industry and trade, in turn, are always alert to these changes, offering alternatives and exploring these niche markets (Garcia, 2003). Thus, the cereal bars has become a practical tool for quick and easy to use and does not require no preparation and can be a source of nutrients considered essential. The nutritional value have also been one of the main aspects considered in the preparation of this product being preferred with high fiber content and low fat or fat-free, but with a high intake of micronutrients (GUTKOSKI et al., 2007). According to Freitas and Moretti (2006), the association between cereal bars and healthy foods is a trend already documented in the food sector, which benefits the market for these products and at the same time requires the industry to search for new ingredients and formulations , seeking products with physico-chemical and nutritional properties capable of providing health benefits (BOWER and Whitten, 2001). However, these foods do not always bring health benefits, because the amounts present of some essential nutrients are not considered significant in relation to recommended.